Operasional Bisnis Pelaku Usaha di Lingkungan Ponpes Ngalah Pasuruan Perspektif Prinsip-Prinsip Ekonomi Islam Umar Chapra - Uyun Nabila; Septi Dwi Arianti; Lilik Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to find out the principles of Islamic economics applied by business actors around the Ngalah Islamic boarding school. This research uses a descriptive method with a qualitative approach using observation and interview analysis tools. The results of the research show that business actors around the Ngalah Islamic boarding school apply the principles. -Islamic economic principles are in accordance with those expressed by M, Umar Chapra, where in running their business business actors adhere to the principle of monotheism as the first foundation, they believe that Allah always watches over what they do so that when conducting business they are always based on caution. And carrying out business fairly by not trading goods and businesses that contain elements of maysir, usury and gharar, establishing a family attitude with other business actors by setting the same prices, as well as the principle of kliafah by managing business sourced from good resources and raw materials. , as well as the principle of al-falah by carrying out business that is oriented towards benefits both for consumers, fellow business actors and for themselves.